Risk Factors for Laryngectomy for Dysfunctional Larynx After Organ Preservation Protocols: A Case-Control Analysis. (March 2021) - Wu, Michael P.; Goldsmith, Tessa; Holman, Allison; Kammer, Rachael; Parikh, Anuraag; Devore, Elliana K.; Emerick, Kevin S.; Lin, Derrick T.; Deschler, Daniel G.; Richmon, Jeremy D.; Varvares, Mark A.; Naunheim, Matthew R.
Objective: (1) To identify factors associated with severe dysfunctional larynx leading to total laryngectomy after curative treatment of head and neck squamous cell carcinoma and (2) to describe swallowing and voice outcomes. Study Design: Retrospective single-institution case-control study. Setting: Tertiary care referral center. Methods: A 10-year chart review was performed for patients who had previously undergone radiation or chemoradiation for head and neck mucosal squamous cell carcinoma and planned to undergo total laryngectomy for dysfunctional larynx, as well as a control group of matched patients. Controls were patients who had undergone radiation or chemoradiation for mucosal squamous cell carcinoma but did not have severe dysfunction warranting laryngectomy; these were matched to cases by tumor subsite, T stage, and time from last treatment to video swallow study. Main outcomes assessed were postoperative diet, alaryngeal voice, pharyngeal dilations, and complications. Results: Twenty-six patients were scheduled for laryngectomy for dysfunctional larynx, of which 23 underwent surgery. Originally treated tumor subsites included the larynx, oropharynx, hypopharynx, oral cavity, and a tumor of unknown origin. The median time from end of cancer treatment to laryngectomy was 11.5 years. All cases were feeding tube or tracheostomy dependent or both prior to laryngectomy. As compared with matched controls, cases were significantly less likely to have undergone IMRT (intensity-modified radiotherapy) and more likely to have pulmonary comorbidities. Eighty-nine percent of cases with follow-up achieved functional alaryngeal voice, and all were able to have oral intake. Conclusion: Non-IMRT approaches and pulmonary comorbidities are associated with laryngectomy for dysfunction after radiation or chemoradiation.